2011
DOI: 10.1364/oe.19.020886
|View full text |Cite
|
Sign up to set email alerts
|

Phase-stabilized optical frequency domain imaging at 1-µm for the measurement of blood flow in the human choroid

Abstract: In optical frequency domain imaging (OFDI) the measurement of interference fringes is not exactly reproducible due to small instabilities in the swept-source laser, the interferometer and the data-acquisition hardware. The resulting variation in wavenumber sampling makes phase-resolved detection and the removal of fixed-pattern noise challenging in OFDI. In this paper this problem is solved by a new post-processing method in which interference fringes are resampled to the exact same wavenumber space using a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 49 publications
2
101
0
Order By: Relevance
“…Using this reference object, the phase of each A-line can be aligned in post-processing to restore phase stability. To account for unstable triggering of a swept-source sweep, a fiber Bragg grating can be used to generate a wavelength-dependent trigger to synchronize each A-line [142], while instabilities within the wavelength sweep can be calibrated out using a reference interferometer [143].…”
Section: Hardware Methods For Phase Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this reference object, the phase of each A-line can be aligned in post-processing to restore phase stability. To account for unstable triggering of a swept-source sweep, a fiber Bragg grating can be used to generate a wavelength-dependent trigger to synchronize each A-line [142], while instabilities within the wavelength sweep can be calibrated out using a reference interferometer [143].…”
Section: Hardware Methods For Phase Stabilizationmentioning
confidence: 99%
“…Jitter of high-speed scanning mirrors used in point-scanning systems can be a source of instability [140], and the rotational scanning mechanisms in catheter-based OCT imaging are typically very unstable [141]. The imprecise triggering of swept-source lasers can also lead to phase instability within and between scan lines [142,143].…”
Section: Phase Stability Requirementsmentioning
confidence: 99%
“…However, to the best of our knowledge, removal of the residual fixed-pattern noise with these methods has not been demonstrated. Braaf et al demonstrated an effective method to eliminate the residual fixed-pattern noise and improve the phase stability by resampling the wavenumber using a simultaneously recorded calibration signal from an interferometer [8]. Although effective, this method requires another reference calibration signal as well as another digitizer channel.…”
Section: Introductionmentioning
confidence: 99%
“…It has become an essential tool for clinical diagnosis and disease monitoring in ophthalmology and it shows great potential in other clinical areas such as dermatology, cardiology and gastroenterology [2][3][4][5][6][7]. The axial resolution of OCT imaging at moderate numerical aperture is determined primarily by the light source as illustrated by the equation:   …”
Section: Introductionmentioning
confidence: 99%